Social Rating System as a Form of State Control Over Society: Prospects for Implementation and Development, Threats to Realization - Yuliya V. Katrashova; Gleb Yu. Mityashin; Vladimir A. Plotnikov (Управленческое консультирование)
The purpose of the article was a scientifically sound assessment of the advantages and risks of introducing a social rating system into the mechanism of state control over society. The article reveals the concept of social rating and reveals the basic principles of its formation. The degree of influence of the rating assessment on the living conditions of citizens and stimulation of their socially useful behaviour is reflected. Using the example of Chinese experience, the procedure for implementing projects on the implementation of the social rating system was considered, on the basis of which a comparative analysis of the advantages and risks of integrating the concept of social rating into the mechanism of public administration was carried out. During the author’s study, general scientific methods of analysis and synthesis were used, as well as the monographic method and the method of establishing causal relationships.